STANDARDISATION OF SPECIFICATIONS FOR DIFFERENT TROLLING LURES - PILLAl, N SUBRAMONIA; MANOHARADOSS, R S; SULOCHANAN, P (Fishery Technology, 2025)
Fishing experiments were conducted with buffalo horn, wooden and galvanised iron jigs of different lengths and weights rigged in troll lines. It was observed that jigs with 12 em length and 60 g weight were superior to others in luring seer fish. Fish head jigs of 60 g weight showed a higher efficiency index than those of 50 and 70 g tried in these studies